Enzyme Immobilization on Inorganic Surfaces for Membrane Reactor Applications: Mass Transfer Challenges, Enzyme Leakage and Reuse of Materials. Issue 14 (5th June 2018) - Sigurdardóttir, Sigyn Björk; Lehmann, Jonas; Ovtar, Simona; Grivel, Jean‐Claude; Negra, Michela Della; Kaiser, Andreas; Pinelo, Manuel
Abstract: Enzyme immobilization is an established method for the enhancement of enzyme stability and reusability, two factors that are of great importance for industrial biocatalytic applications. Immobilization can be achieved by different methods and on a variety of carrier materials, both organic and inorganic. Inorganic materials provide the advantage of high stability and long service life which, together with the prolonged service life of the immobilized enzyme, can benefit the process economy. However, enzyme immobilization and increased stability often come at the cost of decreased enzyme activity. The main challenges involved in the design of an efficient immobilized enzyme system is to obtain both retention of high enzyme activity, enhanced stability and reusability, which is a complicated task, given the many variables involved, and the large numbers of methods and materials available. Simultaneously, new carrier materials and morphologies are constantly being developed. An investigation of enzyme immobilization systems on inorganic materials, with special emphasis on inorganic membranes, has been conducted in order to evaluate the effects of the immobilization system on the enzyme properties upon immobilization, i.e., activity, stability and reusability. The material properties of the enzyme carriers (particles and membranes) and their effects on the success of immobilization are described here. Furthermore, the reuse of inorganic membranes as enzyme carriers has been investigated and the reported examples show high ability of regeneration. To the best of our knowledge, this is the first review on enzyme immobilization focusing on the three fundamental aspects to consider when dealing with the topic: catalytic properties, enzyme leakage and reusability.Abbreviations : β‐Gal: β‐d ‐galactosidase; ADH: alcohol dehydrogenase; AFM: atomic force microscopy; APTES: 3‐aminopropyltriethoxysilane; APTMS: 3‐aminopropyltrimethoxysilane; BPA: bisphenol A; BSA: bovine serum albumin; CA: carbonic anhydrase; CALB: Candida antartica lipase B; CD: circular dichroism; CDI: carbonyldiimidazole; CLEA: cross‐linked enzyme aggregates; CLSM: confocal laser scanning microscopy; CNT: carbon nanotube; CPG: controlled pore glass; CRL: Candida rugosa lipase; DMeDMOS: dimethyldimethoxysilane; DRIFT: diffuse reflectance Fourier transform infrared; E2: 17β‐estradiol; EDC: N‐ (3‐dimethylaminopropyl)‐ N′ ‐ethylcarbodiimide hydrochloride; EDS: electron dispersive spectroscopy; FDH: formate dehydrogenase; FESEM: field emission scanning microscopy; FT‐IR: Fourier transform infrared spectroscopy; GA: glutaraldehyde; GCSZn: coal fly ashes glass‐ceramic zinc sulfate; GOD: glucose oxidase; GPS: 3‐(glycidyloxypropyl)trimethoxysilane; HDMI: hexamethylene diisocyanate; HRP: horseradish peroxidase; IEP: isoelectric point; IPTES: (3‐isocyanatopropyl)triethoxysilane; IR: infrared spectroscopy; LbL: layer‐by‐layer: MCP: metallic ceramic powder; MeTEOS: methyltriethoxysilane; MF: microfiltration; MML: Mucor miehei lipase; MNP: magnetic nanoparticle; MPTMS: 3‐mercaptopropyltrimethoxysilane; NHS: N ‐hydroxysuccinimidyl; PAH: poly(allylamine hydrochloride); PEI: polyethyleneimine; PEG: polyethylene glycol; PES: polyether sulfone; PM‐IRRAS: polarization modulation infrared reflection absorption spectroscopy; pNPA: para ‐nitrophenyl acetate; pNPP: para ‐nitrophenyl palmitate; PSS: polystyrene sulfonate; PTMS: phenyltrimethoxysilane; ROL: Rhizopus oryzae lipase; SCAD: Saccharomyces cerevisiae alcohol dehydrogenase; SDS: sodium dodecyl sulfate; SDS‐2: sodium dodecyl sulfonate; SEM: scanning electron microscopy; TEM: transmission electron microscopy; TEOS: tetraethoxysilane; TGA: thermogravimetric analysis; TLL: Thermomyces lanuginosa lipase; TMP: transmembrane pressure; TTIP: titanium tetraisoproxide; TVL: Trametes versicolor laccase; UF: ultrafiltration; VTMS: vinyltrimethylsilane Abstract :